Effect of adult feeding substrates on survival and reproduction of Therophilus javanus and Phanerotoma syleptae, two parasitoids of Maruca vitrata - Dannou, E.A.; Azokpota, E.T.; Zanzana, K.; Datinon, B.D.; Sinzogan, A.; Srinivasan, R.; Pittendrigh, B.R.; Tamò, Manuele (Springer, 2022)
The current study was designed to assess the effect of different feeding substrates on survival and reproduction of Therophilus javanus (Bhat & Gupta) (Hymenoptera: Braconidae) and Phanerotoma syleptae Zettel (Hymenoptera: Braconidae) in order to optimize their potential as biological control agents against Maruca vitrata Fabricius (Lepidoptera: Crambidae). Experiments were carried out in laboratory with batches of ten adult females exposed to flowers of either Vigna unguiculata (L) Walp., Tephrosia candida (Roxb.) DC, and Sesbania rostrata Bremek & Oberm, pure honey, honey solution, or saccharide solution to assess parasitoid survival. Parasitoid fecundity was evaluated with separate couples of each species using the same substrates. The highest longevity and mean fecundity were obtained for the parasitoids exposed to Tephrosia candida flowers, while there was no difference between control (starved adults) and adults fed using S. rostrata flowers. The putative nutritional compounds of different flowers used in our study affected the biological parameters and performance of these parasitoids differently. Flowers of Tephrosia candida can serve as feeding substrates to both P. syleptae and T. javanus. This study suggests the possibility of using host plants at the flowering stage as a release point for the deployment of the two parasitoids in a classical biological control programme against M. vitrata.